Acute edematous colitis - Matteucci, Pablo; Perdomo, Roberto; Harretche, Martín; Chiossoni de Filgueira, Martha; Xavier, Artigas (Cirugía del Uruguay, 1976)
The edematous acute colitis, is a segmentary disease presumibly of allergic origin. The authors. present four cases pointing out sorne aspects of the pathology and clinic, emphasizing that in the absence of necrosis the lesion dissapear completely with antiallergics and corticoids.